The Role of Financial Performance in Moderating the Influence of Corporate Governance on Company Value - Tilofa, Livia; Nidia Anggreni Das; Rita Dwi Putri (Basic and Applied Accounting Research Journal, 2024)
This study aims to explore and assess how Financial Performance moderates the impact of Corporate Governance on Company Value. Corporate governance is represented by managerial ownership, institutional ownership, and the remuneration committee. The study focuses on manufacturing companies in the basic industrial and chemical sectors listed on the IDX between 2018 and 2022. A purposive sampling technique was employed to select 140 samples for analysis. Structural Equation Modeling-Partial Least Square (SEM-PLS) through SmartPLS 3.0 software was utilized for data analysis. The findings indicate that Managerial Ownership and Institutional Ownership do not have a significant partial effect on Company Value, while the Remuneration Committee does influence Company Value. Interestingly, Managerial Ownership and Institutional Ownership do not directly impact Company Value, even when moderated by Financial Performance.